2022
DOI: 10.1108/jme-10-2021-0185
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to multicultural education in Iran

Abstract: Purpose This paper aims to identify and investigate barriers to multicultural education in Iran. Design/methodology/approach This research is a qualitative research that was done using the phenomenological method. Participants included all experts and key informants in the field of multicultural education in the country who were selected as a statistical sample in different stages of the research using purposeful sampling. The semi-structured interview was used to collect information. Two ways, including mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Consequently, all participants believed the government views MT education as a threat, using justi cations such as considering Persian the language of knowledge, promoting streamlined communication, facilitating administrative processes, and strengthening national identity. This is also in line with Hassanpour et al (2022) ndings. One of the participants stated:…”
Section: Centralization (Ec)supporting
confidence: 92%
See 2 more Smart Citations
“…Consequently, all participants believed the government views MT education as a threat, using justi cations such as considering Persian the language of knowledge, promoting streamlined communication, facilitating administrative processes, and strengthening national identity. This is also in line with Hassanpour et al (2022) ndings. One of the participants stated:…”
Section: Centralization (Ec)supporting
confidence: 92%
“…Iran is a multicultural and multilingual society that has hosted many different ethnic and linguistic groups throughout its history, namely, Persians, Turks, Kurds, Baluchis, Arabs, Gilaks, Mazanis, Armenians, and Turkmens (Hassanpour et al, 2022;Atabaki, 2005). Despite this diversity, research conducted by Aliakbari & Darabi (2012) and Aliakbari & Khosravian (2014) has revealed that Persian holds the position as the predominant language in Iran, accounting for 51% of usage across 12 provinces out of 31.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Iran, in the religious area of education, Islam (Shiite) has dominated the curriculum, and the traces of other Islamic and non-Islamic religions are not visible or very insignificant (Hassanpour et al , 2022). The education system should move toward religious diversity because, according to Topidi (2020), education represents an ideal path to maintain and develop one’s identity, mainly when belonging to a religious minority.…”
Section: Introductionmentioning
confidence: 99%
“…tudies on multi-religion is crucial for promoting tolerance, coexistence, and freedom (Hassanpour et al, 2022). In Indonesia, society adheres to various religions, including Islam, Protestantism, Catholicism, Hinduism, Buddhism, and Confucianism.…”
mentioning
confidence: 99%